Medical students’ experience of culturally diverse family presence during resuscitation simulation - Kyung Hye Park; Jannet J. Lee-Jayaram; Benjamin W. Berg (Korean Journal of Medical Education)
Purpose This report describes the development of a simulation scenario for medical student that incorporates cultural diversity within the context of family presence during resuscitation (FPDR). Methods Using a hybrid simulation approach, we designed a scenario focusing on communication with a family that immigrated from Korea to the United States during cardiopulmonary resuscitation (CPR). The scenario objectives were for learners to perform CPR with family presence, communicate with the family, and understand and negotiate cultural needs. Following a pilot scenario with two inexperienced volunteer medical students as learners, the program was evaluated through anonymous surveys and informal focus group feedback. Results Students noted that this simulation differed from previous experiences as compared with emphasizing family communication rather than patient diagnosis or treatment. Students valued experiencing the practical application of cultural competence concepts. The suggestions for scenario improvement included balancing two student participation roles, adjusting the timeline, and utilizing a standardized family member. Conclusion This pilot study suggests that an FPDR simulation program can be effectively repeated with multiple medical students and applied to CPR simulations involving diverse cultural backgrounds.